2009
DOI: 10.1111/j.1742-1241.2008.01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of physical activity in older patients: a review

Abstract: As the number of elderly persons in our country increases, more attention is being given to geriatric healthcare needs and successful ageing is becoming an important topic in medical literature. Concept of successful ageing is in first line on a preventive approach of care for older people. Promotion of regular physical activity is one of the main non-pharmaceutical measures proposed to older subjects as low rate of physical activity is frequently noticed in this age group. Moderate but regular physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
254
0
36

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(297 citation statements)
references
References 134 publications
(120 reference statements)
7
254
0
36
Order By: Relevance
“…The failure of measures such as weight or BMI in differentiating efficiency could support current evidence in favor of disregarding measures such as BMI as an indicator of risk of mortality in the elderly, with other factors, such as a sedentary lifestyle, being more important 52 . These results, in agreement with those of other authors 53 , suggest the importance of investigating the target population's health needs, activity dose, and demographics before implementing programs, especially if differences between population features have been identified 9,21,54 . The establishment of specific groups of individuals may mitigate the discrepancy between ideal versions of programs and their practical implementation.…”
Section: Discussionsupporting
confidence: 82%
“…The failure of measures such as weight or BMI in differentiating efficiency could support current evidence in favor of disregarding measures such as BMI as an indicator of risk of mortality in the elderly, with other factors, such as a sedentary lifestyle, being more important 52 . These results, in agreement with those of other authors 53 , suggest the importance of investigating the target population's health needs, activity dose, and demographics before implementing programs, especially if differences between population features have been identified 9,21,54 . The establishment of specific groups of individuals may mitigate the discrepancy between ideal versions of programs and their practical implementation.…”
Section: Discussionsupporting
confidence: 82%
“…Age-specific analysis showed that the relative benefits of cycling are highest in the older age categories. This may have been even more pronounced if we had taken into account that the relative risks of physical activity may be larger for the elderly (Vogel et al 2009). The empirical evidence for higher relative risks in elderly related to long-term exposure to air pollution is weak; for example, in the large American Cancer Society study there were no differences in relative risk for PM 2.5 (Pope et al 2002).…”
Section: Overall Discussionmentioning
confidence: 99%
“…Physical activity-bodily movement produced by the skeletal muscles that results in energy expenditure [1]-prevents or delays onset of many negative physical and mental health outcomes common among older adults, including but not limited to diabetes, cardiovascular disease, breast and colon cancer, arthritis, dementia, declines in physical capacity, falls, loss of independence, and frailty [2][3][4][5]. Despite these protective benefits, fewer than one in four Americans age 65 and over meet recommended physical activity guidelines [6], and nearly a third report engaging in no leisure-time physical activity in the past month [7].…”
Section: Introductionmentioning
confidence: 99%